Application of Parlimentary Treshold to the Sustainability of Political Parties from a Human Rights Perspective - Yani, Ahmad Yani (Jurnal Legisci, 2023)
Law has close relevance to justice. Elections in Indonesia's democratic state are a process of peaceful transfer of power carried out periodically and per the principles outlined by the constitution. There are times when people want supervision of the government. However, there are also times when people get tired of their representatives who continue to behave because of seemingly unlimited power. One of the issues hotly discussed when approaching the 2019 election yesterday was raising the Parliamentary Threshold. Based on this description, a formula can be drawn: How does the Parliamentary threshold affect the existence and development of political parties? The research method used is Normative Legal Research. Parliamentary threshold is recognized as one of many ways to simplify political parties. However, PT must also be recognized as one of the most effective ways because it does not threaten the existence of any particular political party.